Improvement of hole injection characteristics in wet-processed organic field-effect transistor based on oxidation of silver electrode surface. (28th January 2022) - Minagawa, Masahiro; Sakai, Ryuichi; Takashima, Kota; Ishizaki, Taku; Kobayashi, Kanta; Sone, Shinnosuke; Yamanashi, Yusuke; Kondo, Masakazu; Shinbo, Kazunari
Abstract: Source–drain electrodes for organic field-effect transistors (OFETs) were fabricated with Ag nanoink on a Si wafer with a 300 nm thick oxide layer using the repellent patterning method, and a depth-profile analysis of the composition and physical properties of the electrode surface was performed once the electrode was oxidized by UV–ozone irradiation. Additionally, OFETs with a wet-processed electrode and 9, 10-diphenylanthracene layer were fabricated, and their electrical characteristics were measured. The chemical composition of the Ag electrode surface changed to silver oxide (Ag2 O or AgO) due to the longer oxidation treatment time, and the work function value increased. In the OFET with the electrode oxidized for 600 s, increased drain current ∣ I D ∣ was observed around a gate voltage of 0 V. Furthermore, good OFET characteristics were obtained [maximum ∣ I D ∣ = 326.2 μ A, mobility μ  = 0.91 cm 2 V −1 ·s −1 ], which were similar to those of the OFETs manufactured using a dry process.